2018
DOI: 10.1016/j.jagp.2018.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Hearing Loss and Its Association with Depression in Later Life

Abstract: ARHL was associated with increased depressive symptoms in older adults. Future studies should investigate whether treatment of ARHL may be an effective prevention and/or therapeutic strategy for depressive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
76
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 36 publications
9
76
2
2
Order By: Relevance
“…Moreover, we found that chronic symptom trajectory class membership was associated with a higher increase in hearing difficulties and multimorbidity, probably because of reward loss on a daily basis (e.g., difficulty in holding conversations), regardless of sex (Brewster et al, 2018;Rote et al, 2015). On the other hand, subclinical trajectory class membership was distinguished by a higher increase in visual difficulties over time probably due to a moderate loss of reward (i.e., visual impairment limits independence) and sensory disability (Freeman et al, 2016;Tolman et al, 2005).…”
Section: Discussionmentioning
confidence: 76%
“…Moreover, we found that chronic symptom trajectory class membership was associated with a higher increase in hearing difficulties and multimorbidity, probably because of reward loss on a daily basis (e.g., difficulty in holding conversations), regardless of sex (Brewster et al, 2018;Rote et al, 2015). On the other hand, subclinical trajectory class membership was distinguished by a higher increase in visual difficulties over time probably due to a moderate loss of reward (i.e., visual impairment limits independence) and sensory disability (Freeman et al, 2016;Tolman et al, 2005).…”
Section: Discussionmentioning
confidence: 76%
“…ARHI is characterised by a non-syndromic bilateral, sensorineural hearing loss that progresses with increasing age and is an established risk factor for depression [6][7][8] and dementia [9][10][11][12] . Hearing loss was ranked fourth in the latest study into the Global Burden of Diseases 13 , yet hearing amplification devices are the only treatment option currently available for ARHI.…”
Section: Age-related Hearing Impairment (Arhi) Is the Most Common Senmentioning
confidence: 99%
“…Considering the fact that GI subjects had tinnitus-associated hearing loss and the known relationship between hearing loss and age (14) , the results of the comparison between groups regarding age showed expected statistical differences, with higher mean in GI (*p<0.001). The prevalence of hearing loss, and consequently of tinnitus, is known to increase with age, regardless of exposure to occupational noise or lack thereof (15) .…”
Section: Discussionmentioning
confidence: 99%